Assessing common bottlenose dolphin (Tursiops truncatus) population structure in Mississippi Sound and coastal waters of the north central Gulf of Mexico. Issue 10 (16th July 2021) - Vollmer, Nicole L.; Rosel, Patricia E.; Mullin, Keith D.; Schwacke, Lori H.; Garrison, Lance P.; Balmer, Brian C.; Barry, Kevin; Martinez, Anthony; Quigley, Brian M.; Sinclair, Carrie; Speakman, Todd R.; Wicker, Jesse; et al.
Abstract: Population structure of highly mobile marine organisms can be complex and difficult to study, but it is important to understand how populations partition themselves within their environment for accurate assessment of both natural and anthropogenic impacts and successful management. The 2010 Deepwater Horizon oil spill negatively impacted common bottlenose dolphins ( Tursiops truncatus ) within Mississippi Sound and the surrounding north central Gulf of Mexico (GOMx); however, little was known about their underlying population structure in these waters. Thus, it was unclear how many demographically independent populations were affected by the spill. Common bottlenose dolphin samples were collected throughout inshore waters of Mississippi Sound and coastal waters of the north‐central GOMx. Mitochondrial DNA control region sequence data and 19 nuclear microsatellite loci were analysed to determine how many populations are present and characterize their range throughout these waters. Bayesian clustering and migration analyses identified two genetically distinct and demographically independent populations: one predominantly inhabiting Mississippi Sound and adjacent coastal waters, and a second population extending generally from offshore of Mobile Bay, Alabama, east along the Florida Panhandle. Neither of these populations align with the currently delineated management stocks previously used to estimate impacts from the oil spill on common bottlenose dolphins in this portion of the GOMx. These results suggest that revisions may be necessary so that management stocks accurately represent the demographically independent populations present in these waters. Furthermore, better comprehension of underlying population structure will enhance impact assessments on common bottlenose dolphins and provide more appropriate baseline data to support future restoration and conservation objectives.